High power ultra-stable mid-IR frequency combs - (:unkn) unknown (My University, 2025)
In the last decade, optical frequency combs from femtosecond lasers have revolutionized numerous research areas in optical metrology, spectroscopy, and time/frequency research. By providing a direct and phase-coherent link between microwave and optical frequencies, they enabled measurements of optical frequencies with extreme precision. They led to the development of novel optical atomic clocks with unprecedented frequency stability, and also triggered impressive progresses in broadband high-resolution spectroscopy. In a typical commercial frequency comb system, an ultrafast laser operating at 800-nm, 1-µm, or 1.5-µm is launched into a highly nonlinear fiber and generates an octave-spanning supercontinuum spectrum. Due to the pump wavelength, the supercontinuum is usually limited to the visible and near-infrared spectral region. The development of sources providing stable mid-infrared frequency combs in the 2-10 µm spectral region is one of the major current research trends in optics and photonics. Such sources give access to a spectral region in which many relevant molecules have characteristic absorption lines, the so-called “fingerprint region”. In this region, the detection sensitivity can be strongly improved, which allows for faster monitoring and higher precision in gas sensing. Moreover, the Earth atmosphere has a transmission window in the 3-5 µm spectral region where the dominant atmospheric absorbers like CO2 and water vapor absorb poorly, which enables remote detection of environment- or security-relevant substances like toxics or explosives. The wavelength limitation is caused by a lack of suitable ultrafast gain materials operating at long wavelengths. Commonly used gain materials for ultrafast frequency combs are Ti:sapphire (800 nm), Yb-doped gain materials (1 µm), Er-doped gain materials (1.5 µm), and recently Tm-doped gain materials (2 µm). Optical parametric oscillators (OPOs) are an excellent method for overcoming the wavelength limitations and generating radiation in the mid-IR spectral region. In this SNF project, we want to contribute to the development of powerful ultra-stable mid-IR frequency combs. Ultrafast thin disk lasers (TDLs) have been generating the highest power levels from any ultrafast oscillator technology for many years. The combination of their high average power and short pulse duration makes them very attractive for pumping nonlinear parametric systems. In a first step, we want to investigate low noise CEO-stabilized TDLs and increase their output power levels. In a second step, we will use these sources to pump mid-IR OPOs, and evaluate and optimize their frequency stability.
Keywords: Mid-infrared; Molecular fingerprinting; Ultrafast lasers; Optical parametric oscillator; Noise and stabilization; Optical frequency comb; Thin disk lasers